Entertaining Impoliteness in Indonesia Lawak Klub: A Metaphor of Sport Games - Murni, Sri Minda (LINGUA: Jurnal Bahasa dan Sastra, 2014)
Studies have shown that impolite utterances are very often used by a speaker to get power over his/her addressee. They also have proved that impoliteness is used by a speaker to entertain his/her addressee. These studies have found out that power and entertainment serve as two distinct effects in linguistic impolitenessstudies. This article presents a simultaneous effects of power and entertainment through the use of impolite utterances in Indonesia Lawak Klub (ILK). The finding shows that impolite utterances are used by comedians to get power over another (comedians) in their goal to entertain the audience. It implies that power and entertainment can be targetted at the same time through impolite utterances.